ZnMgSe:Cr²⁺ single crystal: a novel material for active elements of tunable IR region lasers (rapid communication) - Zagoruiko, Yu.A.; Kovalenko, N.O.; Fedorenko, O.A.; Khristyan, V.A. (Functional Materials, 2008)
Obtained is a new thermostable material for active elements of tunable IR-lasers - Zn₁₋ₓMgₓSe:Cr²⁺, single crystals. The position of the absorption band of Cr²⁺ ions in wurtzite-type Zn₀.₇₉Mg₀.₂₁Se matrix is established. Отримано новий термостабільний матеріал для активних елементів ІЧ-лазерів з перестроюванням частоти монокристалічний Zn₁₋ₓMgₓSe:Cr²⁺. Визначено смугу поглинання іонів Cr²⁺ у матриці Zn₀.₇₉Mg₀.₂₁Se зі структурою типу "вюртцит". Получен новый термостабильный материал - монокристаллический Zn₁₋ₓMgₓSe:Cr²⁺, для активных элементов перестраиваемых лазеров ИК-диапазона. Определено положение полосы оптического поглощения ионов Cr²⁺ в матрице Zn₀.₇₉Mg₀.₂₁Se со структурой типа "вюртцит".